Pengaruh Penggunaan E-LKPD Dalam Pembelajaran Matematika Terhadap Kemampuan Penalaran Peserta Didik Kelas VIII SMP - Ahmar, Safaqa; Soro, Slamet (Edumatica : Jurnal Pendidikan Matematika, 2023)
This study aims to see the effect of the use of Electronic Student Worksheets on the reasoning ability of 8th-grade junior high school students in mathematics learning. The type of research used is quantitative research with Quasi-Experimental methods. The population in this study is all grade VIII students for the 2022/2023 school year and sampling using the Cluster Random Sampling technique. The samples used were 2 homogeneous classes, namely class VIII-F as an experimental class and VIII-E as a control class with 26 students each. Data collection was conducted using a reasoning ability test instrument in the topic of polyhedra as a posttest, with the questions in the instrument being in the form of essay-type responses. The prerequisite tests for data analysis are normality tests with the Product-Moment pearson formula and homogeneity tests with the Cronbach Alpha formula, hypothesis tests using t-tests and continued with influence testing using effect size tests. The results showed that the reasoning ability of experimental class students was higher than students in the control class.Â  The impact of using Electronic Student Worksheets on students' reasoning ability is moderate in mathematics learning.